The peculiarities of neurotic children's families - Nasvytienė, D. (Psichologija, 1990)
The present paper reveals some aspects of the family environment of a neurotic child. 'I'wenty four families ( 38 persons ) of neurotic children have been studied. The experimental investigation has shown that neurotic children's parents tend to be hyperprotective, less punishing, lacking selfconfidence in children's upbringing and preferring feminine features of character in their children ( though the majority of neurotics were boys ) . It has also been pointed out that some personality traits and biographic data of the families such as the relatively late time of parenthood, the fact of on unwanted child, boys' education in the broken family are of certain significance.
Keywords: children; neurotic; family